Prevalence and Associated Factors of Iron Deficiency Anemia in Children Under Two Years: A Comprehensive Analysis - Rasool, Abeer Mansour Abdel; Hameed, Abdul Hammeed Subhi; Younes, Ahmed Ibrahim (American Journal of Biomedicine and Pharmacy, 2025)
Introduction: Iron deficiency is the most common nutritional deficiency ailment across the world and is responsible for 90% of childhood anemia, it. Consequently, IDA etiology comprises of physiological and nutritional variables. This study also seeks to establish the frequency of IDA, its causes and methods of preventing the condition amongst children below the age of two years. Patients and method: This cross-sectional, non-observational study included 110 infants less than two years old presenting with IDA. Specific inclusion criteria regarded infants up to twelve months. The variables captured include; One hundred infants with normochromic normocytic mean values were used as the control group. Results: The study identified several clinical features of iron deficiency anemia (IDA) among participants. revealed the highest incidence of IDA in infants aged 9-12 months. Conclusion: Inadequate iron consumption in infants under six months, often resulting from premature weaning, precipitates iron deficiency anemia (IDA), which peaks between 9 and 12 months, occasionally requiring transfusions for certain affected infants.